TATA KELOLA, KOMPENSASI CEO, KARAKTERISTIK CEO, ACCOUNTING IRREGULARITIES DAN TAX AGGRESSIVENESS - Ririn Juliawaty; Christina Dwi Astuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this research is to examine the effect of corporate governance, CEO characteristic, CEO compensation, and accounting irregularities on tax aggressiveness. The dependent variable in this research is tax aggressiveness, while the independent variable in this research are corporate governance, characteristic CEO and CEO compensation.This study used secondary data with entire population manufacture companies listed at the Indonesia Stock Exchange (BEI) for 2015 -2017. The research sample are consists of 37 companies. The sampling method used to determine the sample is purposive sampling. The analysis model used in this research is multiple regression of panel data.Based on analytical results concluded that independent director have a significant and negative effect on tax aggressiveness while accounting irregularities has a significant and positive effect on tax aggressiveness. The board size, CEO compensation, age, and CEO tenure have no significant effect on tax aggressiveness.